2018
DOI: 10.1124/pr.117.013706
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Neuropsychiatric Events and Recreational Use of Efavirenz and Other HIV-1 Antiretroviral Drugs

Abstract: Efavirenz is a highly effective HIV-1 antiretroviral; however, it is also frequently associated with neuropsychiatric adverse events (NPAE) that include abnormal dreams, sleep disturbances, nervousness, anxiety, depression, and dizziness. The incidence of NPAEs upon initiation of treatment with efavirenz-containing medications is high, exceeding 50% in most studies. Although the NPAEs tend to decrease after the first month in many patients, they persist for long periods of time in others. Efavirenz-based treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 271 publications
0
39
0
Order By: Relevance
“…18,33 Additionally, research designed to assess the neuropsychiatric effects of different ART regimens and algorithms that predict likelihood of ART discontinuation are required. 34 This study indicates that pre-ART screening for psychological risk factors might be valuable particularly when EFV is being considered given that EFV-free options that induce fewer neuropsychiatric AE are available even in resource-limited settings.…”
Section: Predictor Of Discontinuation Of Efavirenz In the Ukmentioning
confidence: 85%
“…18,33 Additionally, research designed to assess the neuropsychiatric effects of different ART regimens and algorithms that predict likelihood of ART discontinuation are required. 34 This study indicates that pre-ART screening for psychological risk factors might be valuable particularly when EFV is being considered given that EFV-free options that induce fewer neuropsychiatric AE are available even in resource-limited settings.…”
Section: Predictor Of Discontinuation Of Efavirenz In the Ukmentioning
confidence: 85%
“…(6) In the current study, lamivudine and tenofovir, prescribed as first line HIV therapy, were the most prevalent drugs in the treatment regimens assessed in Paraná. Efavirenz, that ranks next, is associated with neuropsychiatric reactions, (9) but remains as the component of initial treatment for patients with satisfactory results and good tolerance to the drug. (10) It is also indicated preferably as the initial regimen for child-bearing age women.…”
Section: ❚ Resultsmentioning
confidence: 99%
“…Efavirenz is a non-nucleoside reverse transcriptase inhibitor which is combined with other antiretroviral medications for use in the treatment of HIV, and it has been prescribed as part of first-line therapy in South Africa since 2013. Efavirenz, like lysergic acid diethylamide (LSD), has activity at the 5HT-2A receptor (Cavalcante et al, 2017;Dalwadi et al, Schetz, 2018;Gatch et al, 2013;Möller et al, 2018). In support of its LSD-like psychoactivity, it has been reported that efavirenz has been smoked in South Africa for its "hallucinogenic and relaxing effect" (Marwaha, 2008).…”
Section: Introductionmentioning
confidence: 99%